Faktor-faktor yang berhubungan dengan siklus menstruasi pada remaja putri - Rahmawati, Cori Dwi; Sunarsih, Sunarsih; Susilawati, Susilawati (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2025)
Background: Menstrual disorders are common among adolescents worldwide, with a prevalence of approximately 45% in early adolescence among women. Furthermore, 13.7% of Indonesian adolescents aged 10-17 experience irregular menstruation. Factors associated with menstrual cycle disorders include stress, nutritional status, hemoglobin levels, physical activity, and sleep duration. Objective: To identify factors associated with menstrual cycle disorders in adolescent girls. Purpose: To determine factors associated with menstrual cycle disorders in adolescent girls. Method: This quantitative study used a cross-sectional design. The population in this study was all 125 female students of SMP Negeri 44 Gunung Sulah Bandar Lampung. The sampling technique used purposive sampling with 55 respondents. Bivariate analysis used the chi-square test. Results: The chi-square test obtained a p-value of 0.198 > 0.05 for the variables of menarche age and menstrual cycle. Furthermore, a p-value of 0.000 < 0.05 was obtained for the variables of stress and menstrual cycle. The chi-square test results showed a p-value of 0.000 < 0.05 for the variables of nutritional status and menstrual cycle. Conclusion: Stress and nutritional factors influence the menstrual cycle, but age at menarche does not affect the menstrual cycle in adolescents.   Keywords: Age at Menarche; Menstrual cycle; Nutritional status; Stress level.   Pendahuluan: Gangguan menstruasi merupakan hal yang umum terjadi pada kelompok remaja di dunia dengan prevalensi pada wanita di awal masa remaja sekitar 45%. Selain itu, remaja di Indonesia usia 10-17 tahun mengalami masalah menstruasi tidak teratur sebanyak 13.7%. Faktor-faktor yang berhubungan  dengan gangguan siklus menstruasi meliputi stres, status  gizi,  kadar hemoglobin, aktivitas  fisik,  dan  durasi  tidur. Tujuan: Untuk mengetahui faktor-faktor yang berhubungan dengan siklus  menstruasi pada remaja putri. Metode: Penelitian kuantitatif dengan desain penelitian cross sectional. Populasi dalam penelitian ini adalah seluruh seluruh siswi remaja putri SMP Negeri 44 Gunung Sulah Bandar Lampung sebanyak 125 orang dengan teknik pengambilan sampel menggunakan purposive sampling sebanyak 55 responden. Analisis bivariat menggunakan uji chi square. Hasil: Uji chi square diperoleh p value  0.198 > 0.05 pada variabel faktor usia menarche dan siklus menstruasi. Selain itu, diperoleh juga nilai p 0.000 < 0.05 pada variabel faktor stres dan siklus menstruasi. Kemudian hasil uji chi square menunjukkan nilai p 0.000 < 0.05 pada variabel status gizi dan siklus menstruasi. Simpulan: Faktor stress dan faktor gizi mempengaruhi siklus menstruasi, namun faktor usia menarche tidak memengaruhi siklus menstruasi pada remaja.   Kata Kunci: Siklus menstruasi; Status gizi; Tingkat stress; Usia menarche.